Estrategias metodológicas para fortalecer estilos de aprendizaje sensoriales en estudiantes de sexto grado, Escuela Fiscomisional “San Juan Bautista”, Catamayo 2023- 2024 - Chamba Cango, Guisella Verónica (2024)
The present study on Methodological strategies to strengthen sensory learning styles, had as general objective: To determine how methodological strategies influence the strengthening of sensory learning styles in sixth grade “B” students, of the Fiscomisional Education Unit “San Juan Bautista”, Catamayo 2023-2024, throung methodological strategies to strengthen sensory learning styles; as specific objectives it was proposed: first, Diagnose the current reality in relation to the application of methodological strategies for strengthening sensory learning styles in students; second, Design a didactic guide using a diversity of methodological strategies to strengthen sensory learning styles in students and third, Evaluate the inflluence of methodological strategies that were addressed in the classroom for strengthening sensory learning styles. The present research was descriptive with a mixed approach and non-experimental design, and methods used were: desccrptive-statistical, inductive, analytical, heuristic and synthetic, the techniques used were: direct observation and survey, in addition to instruments such as: the direct observation guide and the questionnaire. The sample consisted of 1 teacher and 24 sixth grade “B” students. AT the conclusion of the study, it was determined that the educational institution in question does not take into account learning styles and does not take into account their imporance. It is essential to point out the value of these styles, not only in the educational sphere, but also in the personal and social spheres, as the allow each person to develop specific skills and also help teachers to investigate alternative methodologies to apply.